Phase variation of manganese oxide in the MnO@ZnO nanocomposite with calcination temperature and its effect on structural and biological activities - Shatarupa Basak; Md Salman Haydar; Suranjan Sikdar; Salim Ali; Modhusudan Mondal; Ankita Shome; Kushankur Sarkar; Swarnendu Roy; Mahendra Nath Roy (Scientific Reports, 2023)
Abstract Having powerful antibacterial and antioxidant effects, zinc oxide and manganese oxide nanomaterials are of great interest. Here we have synthesized manganese oxide decorated zinc oxide (MZO) nanocomposites by co-precipitation method, calcined at different temperatures (300–750 °C) and studied various properties. Here the crystalline structure of the nanocomposite and phase change of the manganese oxide are observed with calcination temperature. The average crystalline size increases and the dislocation density and microstrain decrease with the increase in calcined temperature for the same structural features. The formation of composites was confirmed by XRD pattern and SEM images. EDAX spectra proved the high purity of the composites. Here, different biological properties change with the calcination temperature for different shapes, sizes and structures of the nanocomposite. Nanomaterial calcined at 750 °C provides the best anti-microbial activity against Escherichia coli, Salmonella typhimurium, Shigella flexneri (gram-negative), Bacillus subtilis and Bacillus megaterium (gram-positive) bacterial strain at 300 µg/mL concentration. The nanomaterial with calcination temperatures of 300 °C and 450 °C provided better antioxidant properties.